Cinematic Rendered Computed Tomography Imaging Enhances 3D Visualization of Upper Extremity Arteriovenous Malformation - Balazs C. Lengyel; Alan B. Lumsden; Ponraj Chinnadurai (Methodist DeBakey Cardiovascular Journal)
Inspired by the quality of computer-rendered images in the animated movie industry, cinematic rendering (CR) is a novel image visualization technique using proprietary rendering algorithms that simulate the propagation and interaction of light rays passing through 3-dimensional (3D) volumetric data, resulting in a photorealistic representation of bodily organs and vasculature.1,2 Due to its more realistic representative and intuitive format, it has become part of medical education, especially 3D anatomy teaching, patient education, and communication.3,4 It also plays an important role in the diagnostics and treatment planning for complex vascular pathologies, especially malformations.5 This short report highlights the additional diagnostic and clinical value of this image visualization technique by showing its value in treatment planning in a case of arteriovenous malformation (Figure 1).